Halogen-free flame-retardant nylon composite material and preparation method thereof
Through the blending extrusion process and specific additives, halogen-free flame-retardant nylon composite materials were prepared, which solved the problem of flame-retardant instability caused by the ‘wick effect’ in MCA flame-retardant nylon materials, and achieved the stability of the material to reach the UL94 V0 level, and had good economic and operability.
Patent Information
- Application Number
- CN202510034143.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The existing MCA flame-retardant nylon materials are prone to 'wick effect' during the production process, resulting in unstable flame retardant effect and it is difficult to reach the UL94 V0 level.
Using the blend extrusion method, a halogen-free flame-retardant nylon composite material was prepared by melt extrusion process of twin screw machine using nylon 66 resin, sorbitol acetal nucleating agent, N,N'-bis(2,2,6,6-tetramethyl-4-yl)-1,3-phthalamide heat stabilizer and distilled water as dispersant.
It effectively solves the problem of 'wick effect', ensures the flame retardant stability of the material, can stably reach the UL94 V0 level, and the raw materials are commercially available, have simple process and low cost, which is suitable for applications in the electronic and electrical industry.
Smart Images

Figure BDA0005235055200000021 
Figure BDA0005235055200000031 
Figure BDA0005235055200000081
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials and relates to a halogen-free flame-retardant nylon composite material and a preparation method thereof. Background Art
[0002] Nylon, also known as polyamide, is one of the five major engineering plastics. It has excellent impact resistance, heat resistance, abrasion resistance, chemical resistance and electrical properties. It is a widely used thermoplastic engineering plastic.
[0003] Melamine cyanurate (MCA) is a nitrogen-based halogen-free flame retardant with excellent performance, especially suitable for non-reinforced nylon materials. Its flame retardant mechanism is different from other flame retardants. MCA relies on rapidly improving the fluidity of flame-retardant nylon materials when nylon burns, and taking away a large amount of combustion heat through the dripping phenomenon during combustion, thereby achieving a flame retardant effect.
[0004] However, this flame retardant mechanism has very strict requirements on the production formula and process of nylon materials. It is easy to produce a "wick effect" due to the agglomeration of flame retardants or the introduction of other incompatible impurities, which not only delays the dripping phenomenon of burning, but also causes the molten droplets with flames to ignite the absorbent cotton below, causing the UL94 V0 test to fail. Experience shows that as long as there is 0.01% of agglomeration or infusible material forming a "wick" inside, it can burn and drip to ignite the absorbent cotton, and can only reach the UL 94V2 level.
[0005] However, even in the application of non-reinforced MCA flame-retardant nylon, necessary additives such as heat stabilizers and nucleating agents still need to be added to ensure the use needs of most customers, especially thin-walled and high-production electronic and electrical products, such as connectors, coil skeletons, cable ties, etc., which have extremely stringent requirements on material fluidity and production cycle. However, the addition of some conventional functional additives greatly affects the flame retardant effect of the material. At present, the flame retardant effect of MCA flame-retardant nylon produced by many manufacturers on the market is extremely unstable, and the flame retardant level of only V2 is often measured. Therefore, how to improve the flame retardant effect of MCA flame-retardant nylon and meet the application needs of various downstream manufacturers has always been a hot research topic in the industry.
[0006] Some material manufacturers can reduce the "wick effect" and improve the flame retardant effect by optimizing the dispersion process and strengthening the micro-dispersion of flame retardants and other additives in the system. Patent CN101679743A provides a method of using surfactants to improve the dispersibility of MCA so that flame retardant nylon reaches V0. Patent CN115368730A improves the flame retardant effect of nylon by adjusting the pH value of MCA. However, these methods do not fundamentally solve the problem of "wick effect" and there is great production instability. During the production process, the material was initially tested as flame retardant V0, but the final inspection changed it to flame retardant V2.
[0007] Patent CN201910323025.8, by coating a molten mixture of sebacic acid and hexamethylenediamine with a compound flame retardant having an average particle size (D50) less than 3um, improves the compatibility and bonding between the compound flame retardant and nylon 66 resin. Patent CN201910775378.1, by using an amorphous α-olefin copolymer emulsion, nylon and MCA flame retardant are better connected to reduce the possibility of igniting flammable materials when dripping. These methods all solve the "wick effect" by improving compatibility, but in terms of economy and ease of operation, these methods do not have industry competitive advantages. Patent CN201510588777.9 accelerates the crystallization of MCA flame-retardant nylon and improves the rigidity and appearance of the material through the compounding of inorganic-organic nucleating agents, but does not effectively solve the problems of the material's "wick effect" and flame retardant stability.
[0008] How to use a simple and effective production method to make MCA flame-retardant nylon reach a stable UL94 V0 level has become a difficult problem to be solved in the industry. Summary of the invention
[0009] The invention aims at the defects of the prior art, solves the problem of flame retardant stability of halogen-free flame retardant nylon, and provides a halogen-free flame retardant nylon composite material by a co-blending extrusion method.
[0010] The technical solution adopted by the present invention to solve the technical problem is: to provide a halogen-free flame-retardant nylon composite material, which is made of the following raw materials in parts by weight:
[0011]
[0012]
[0013] In the halogen-free flame-retardant nylon composite material of the present invention, the nylon resin is nylon 66, nylon 6, or one or a mixture of other aliphatic polyamides, preferably nylon 66.
[0014] In the halogen-free flame-retardant nylon composite material of the present invention, the halogen-free flame retardant is melamine cyanurate (MCA).
[0015] In the halogen-free flame-retardant nylon composite material of the present invention, the nucleating agent is a sorbitol acetal nucleating agent. The nucleating agent can accelerate the crystallization rate of the nylon material, making it easier to mold and demould. Although the sorbitol acetal nucleating agent is a third-generation polypropylene transparent nucleating agent, experiments have shown that it not only has a certain nucleating effect in MCA flame-retardant nylon, but also does not affect the flame retardancy of the material at all. Different from the traditional nylon nucleating agent that needs to form a crystal nucleus, this type of nucleating agent is very easy to be compatible with nylon. During the processing, it is melted and dispersed together with nylon, and finally forms a nano-level network state, avoiding the generation of the "wick effect".
[0016] In the halogen-free flame-retardant nylon composite material described in the present invention, the heat stabilizer is N,N'-bis(2,2,6,6-tetramethyl-4-yl)-1,3-benzenedicarbamide. This type of heat stabilizer is also called nylon multifunctional additive. The functional groups it contains not only have the effects of anti-oxidation, thermal stability, UV resistance, lubrication, etc., but can also reduce the investment of such functional additives. In addition, this additive can also be highly compatible with nylon through cross-linking amidation, reducing the possibility of MCA flame-retardant nylon igniting flammable absorbent cotton when dripping.
[0017] In the halogen-free flame-retardant nylon composite material described in the present invention, the dispersant is distilled water. During the stirring and mixing process, distilled water can make MCA and other powders evenly adhere to the surface of the nylon resin, thereby playing a better role in dispersing MCA. At the same time, during the high-temperature melting process of nylon, a trace amount of water can promote the appropriate hydrolysis of nylon, improve the fluidity of the material, and remove low-molecular substances that are prone to wick effect by vacuuming, making it easier to melt and drip to take away heat in the flame retardant test, reducing the risk of dripping and igniting absorbent cotton. In the end, the excess water will be pumped away by the vacuum pump and will not remain in the material to affect the performance.
[0018] A method for preparing a halogen-free flame-retardant nylon composite material comprises the following steps:
[0019] ② Weigh the raw materials according to the aforementioned weight ratio;
[0020] ② Add nylon resin and dispersant additives into a high-speed mixer and mix for 3-10 minutes, then add halogen-free flame retardant, nucleating agent, and heat stabilizer and mix for 15-30 minutes;
[0021] ③ The mixture obtained in step ② is placed in a twin-screw machine, melt-extruded, and granulated, wherein the screw aspect ratio is 32-48, and the process conditions are: zone 1 temperature 200-240°C, zone 2 temperature 230-270°C, zone 3 temperature 200-240°C, zone 4 temperature 220-260°C, die head temperature 240-280°C, barrel residence time 0.5-2 minutes, and melt pressure 10-20 MPa.
[0022] The halogen-free flame-retardant composite nylon material of the present invention solves the "wick effect" problem of MCA flame-retardant nylon, has the characteristics of being able to stably reach flame retardancy V0, and has excellent comprehensive physical properties and processing properties. Its raw materials are all commercially available, the preparation process is simple, the cost is relatively low, and it can meet various application requirements of halogen-free flame-retardant nylon in the market, and is particularly suitable for application in the electronic and electrical industry, and has good development prospects. DETAILED DESCRIPTION
[0023] The present invention will be further described below in conjunction with the embodiments.
[0024] For the convenience of description, the nylon resins used in the cases of the present invention are all nylon 66, produced by Zhejiang Huafeng Company, with the trade name EP-158, the flame retardant MCA is produced by Zhejiang Xusheng Company, with the trade name MC-25; the nucleating agent is produced by Milliken Company of the United States, with the trade name 3988; the heat stabilizer is produced by Clariant of Germany, with the trade name S-EED; the dispersant distilled water is homemade. The nucleating agent used in Comparative Example 2 is a long-chain carboxylic acid calcium salt, produced by Klein Company of Germany, with the trade name CAV102. Antioxidant 1171 is a 1:1 compound of antioxidants 1098 and 168, produced by BASF of Germany. The inorganic nucleating agent used in Comparative Example 5 is a mixture of montmorillonite, ultrafine talcum powder and calcium carbonate.
[0025] Example 1.
[0026] 93.2% nylon 66 resin and 0.1% distilled water by weight were placed in a mixing barrel for premixing for 5 minutes, and then 5% flame retardant MC-25, 0.8% nucleating agent 3988 and 0.9% heat stabilizer S-EED were added and stirred for 16 minutes. After that, the mixed materials were placed in a twin-screw extruder for melt mixing, extrusion and granulation. The screw diameter of the twin-screw extruder was 35mm, the ratio of screw length to diameter was set to 32, the extrusion temperatures were 210℃ for zone 1, 240℃ for zone 2, 230℃ for zone 3, 250℃ for zone 4, the die head temperature was 255℃, the residence time was 1-2min, and the pressure was 15MPa.
[0027] Example 2.
[0028] 90.6% nylon 66 resin and 0.2% distilled water by weight were placed in a mixing barrel for premixing for 8 minutes, and then 8% flame retardant MC-25, 0.5% nucleating agent 3988 and 0.7% heat stabilizer S-EED were added and stirred for 22 minutes. After that, the mixed materials were placed in a twin-screw extruder for melt mixing, extrusion and granulation. The screw diameter of the twin-screw extruder was 52mm, the ratio of screw length to diameter was set to 36, the extrusion temperatures were 215℃ for zone 1, 265℃ for zone 2, 250℃ for zone 3, 260℃ for zone 4, the die head temperature was 270℃, the residence time was 1-2min, and the pressure was 13MPa.
[0029] Example 3.
[0030] 89.1% nylon 66 resin and 0.2% distilled water by weight were placed in a mixing barrel for premixing for 7 minutes, and then 10% flame retardant MC-25, 0.3% nucleating agent 3988 and 0.4% heat stabilizer S-EED were added and stirred for 25 minutes. After that, the mixed materials were placed in a twin-screw extruder for melt mixing, extrusion and granulation. The screw diameter of the twin-screw extruder was 65mm, the ratio of screw length to diameter was set to 40, the extrusion temperatures were 220℃ for zone 1, 265℃ for zone 2, 250℃ for zone 3, 240℃ for zone 4, the die head temperature was 265℃, the residence time was 1-2min, and the pressure was 15MPa.
[0031] Example 4.
[0032] 86.8% nylon 66 resin and 0.3% distilled water by weight were placed in a mixing barrel for premixing for 5 minutes, and then 12% flame retardant MC-25, 0.4% nucleating agent 3988 and 0.5% heat stabilizer S-EED were added and stirred for 27 minutes. After that, the mixed materials were placed in a twin-screw extruder for melt mixing, extrusion and granulation. The screw diameter of the twin-screw extruder was 60mm, the ratio of screw length to diameter was set to 44, the extrusion temperatures were 225℃ for zone 1, 255℃ for zone 2, 240℃ for zone 3, 235℃ for zone 4, the die head temperature was 260℃, the residence time was 1-2min, and the pressure was 19MPa.
[0033] Example 5.
[0034] 84.3% nylon 66 resin and 0.4% distilled water by weight were placed in a mixing barrel for premixing for 9 minutes, and then 15% flame retardant MC-25, 0.6% nucleating agent 3988 and 0.6% heat stabilizer S-EED were added and stirred for 21 minutes. After that, the mixed materials were placed in a twin-screw extruder for melt mixing, extrusion and granulation. The screw diameter of the twin-screw extruder was 60mm, the ratio of screw length to diameter was set to 40, the extrusion temperatures were 220℃ for zone 1, 250℃ for zone 2, 235℃ for zone 3, 230℃ for zone 4, the die head temperature was 255℃, the residence time was 1-2min, and the pressure was 14MPa.
[0035] Example 6.
[0036] 81.1% nylon 66 resin and 0.5% distilled water by weight were placed in a mixing barrel for premixing for 7 minutes, and then 18% flame retardant MC-25, 0.2% nucleating agent 3988 and 0.2% heat stabilizer S-EED were added and stirred for 19 minutes. After that, the mixed materials were placed in a twin-screw extruder for melt mixing, extrusion and granulation. The screw diameter of the twin-screw extruder was 75mm, the ratio of screw length to diameter was set to 36, the extrusion temperatures were 215℃ for zone 1, 245℃ for zone 2, 230℃ for zone 3, 230℃ for zone 4, the die head temperature was 250℃, the residence time was 1-2min, and the pressure was 15MPa.
[0037] Comparative example 1.
[0038] Stir 90% nylon 66 resin and 10% flame retardant MC-25 by weight for 25 minutes. Then put the mixed materials into a twin-screw extruder for melting, mixing, extrusion, and granulation. The screw diameter of the twin-screw extruder is 65mm, the ratio of the screw length to the diameter is set to 40, the extrusion temperatures are 220℃ for zone 1, 260℃ for zone 2, 250℃ for zone 3, 240℃ for zone 4, the die head temperature is 260℃, the residence time is 1-2min, and the pressure is 16MPa.
[0039] Comparative example 2.
[0040] 89.3% nylon 66 resin, 10% flame retardant MC-25, 0.3% nucleating agent CAV102 and 0.4% antioxidant 1171 were stirred for 25 minutes. Then the mixed materials were put into a twin-screw extruder for melting, mixing, extrusion and granulation. The screw diameter of the twin-screw extruder was 65mm, the ratio of screw length to diameter was set to 40, the extrusion temperatures were 220℃ for zone 1, 265℃ for zone 2, 250℃ for zone 3, 240℃ for zone 4, the die head temperature was 265℃, the residence time was 1-2min, and the pressure was 15MPa.
[0041] Comparative example 3.
[0042] The weight ratio of 89.3% nylon 66 resin, 10% flame retardant MC-25, 0.3% nucleating agent 3988 and 0.4% heat stabilizer S-EED were stirred for 25 minutes. Then the mixed materials were put into a twin-screw extruder for melting, mixing, extrusion and granulation. The screw diameter of the twin-screw extruder was 65mm, the ratio of screw length to diameter was set to 40, the extrusion temperatures were 225℃ for zone 1, 260℃ for zone 2, 250℃ for zone 3, 240℃ for zone 4, the die head temperature was 260℃, the residence time was 1-2min, and the pressure was 16MPa.
[0043] Comparative example 4.
[0044] 89.3% nylon 66 resin and 0.2% distilled water by weight were placed in a mixing barrel for premixing for 5 minutes, and then 10% flame retardant MC-25 and 0.3% nucleating agent 3988 were added and stirred for 25 minutes. After that, the mixed materials were placed in a twin-screw extruder for melt mixing, extrusion, and granulation. The screw diameter of the twin-screw extruder was 65mm, the ratio of screw length to diameter was set to 40, the extrusion temperatures were 220℃ for zone 1, 265℃ for zone 2, 250℃ for zone 3, 240℃ for zone 4, the die head temperature was 265℃, the residence time was 1-2min, and the pressure was 15MPa.
[0045] Comparative example 5.
[0046] 89.3% nylon 66 resin and 0.2% distilled water by weight were placed in a mixing barrel for premixing for 5 minutes, and then 10% flame retardant MC-25 and 0.4% inorganic nucleating agent were added and stirred for 25 minutes. After that, the mixed materials were placed in a twin-screw extruder for melt mixing, extrusion, and granulation. The screw diameter of the twin-screw extruder was 65mm, the ratio of screw length to diameter was set to 40, the extrusion temperatures were 220℃ for zone 1, 265℃ for zone 2, 250℃ for zone 3, 240℃ for zone 4, the die head temperature was 265℃, the residence time was 1-2min, and the pressure was 17MPa.
[0047] The halogen-free flame-retardant nylon composite materials prepared in the first six embodiments and five comparative examples were tested, and the performance evaluation method and implementation standard were as follows:
[0048] The granulated material is dried in a blast oven at 80℃ for 3-6 hours, and then the dried material is injection molded on an injection molding machine to prepare samples. The injection molding mold temperature is controlled at 80℃. The tensile strength test is carried out according to ASTM D638 standard, the sample size is 180×12.7×3.2mm, the tensile speed is 50mm / min; the bending performance test is carried out according to ASTM D790 standard, the sample size is 128×13×3.2mm, the bending speed is 3mm / min, and the span is 64mm; the cantilever beam impact strength is carried out according to ASTM D256 standard, the sample size is 63.5×12.7×4.2mm, and the notch size is one-fifth of the sample thickness. The melt index is carried out according to ASTM D1238 standard, the test conditions are 275 degrees, and the weight is 5 kg.
[0049] Molding cycle refers to the total time required for an injection molding machine to complete a mold product. The shorter the molding cycle, the higher the efficiency, which is mainly related to the fluidity and demoulding properties of the material. This time, the baked finished product will be directly injection molded in a mold of 32 10×5mm connectors, and the size of the molding cycle will be used to judge the processing performance of the material.
[0050] The flame retardant test was carried out according to the UL94 method, and the sample size was 128×13×1.6mm. In order to verify the stability of the flame retardant performance of the material. Each embodiment and comparative example was tested in 4 groups, with 5 specimens in each group, for a total of 20 times. The sum of the burning time of each specimen and the probability of dripping and burning cotton in these 20 times were counted as a reference for flame retardant stability.
[0051] The comprehensive mechanical properties of the embodiments and comparative examples were evaluated by testing the tensile strength, flexural strength, impact strength, melt index and flame retardancy test. The results are shown in Tables 1 and 2.
[0052] Table 1 Example
[0053]
[0054]
[0055] Table 2 Comparative Examples
[0056]
[0057] From the examples, the halogen-free flame-retardant nylon material of the present invention can stably reach UL94 V0, but when the amount of MCA added is greater than 15%, the total burning time increases and the flame retardant effect decreases. This may be due to the fact that there is too much MCA powder, and the flame retardant is not easy to disperse, resulting in agglomeration, which reduces the material melt index and delays the melting dripping time. The total burning time of Examples 2, 3, and 4 is the shortest, and the flame retardant effect is also the most stable.
[0058] Compared with the comparative example 1 without any additive, the melt index, injection molding cycle and flame retardant effect of the embodiment 3 are better than those of the comparative example 1, indicating that the additive added in the present invention not only improves the processing performance of the material, but also has a good synergistic flame retardant effect with the flame retardant MCA. This point is fully confirmed in the comparative examples 3 and 4.
[0059] Comparative Example 2, in which antioxidants and nucleating agents commonly used in the market are added, has an obvious "wick effect" in terms of flame retardancy results. Not only is the burning time long, but 70% of the test strips drip and burn, making it difficult to stably reach the V0 level.
[0060] In comparative example 5, the added inorganic nucleating agent affects the microstructure of the polymer, plays a wick effect, and intensifies combustion. It also increases the viscosity of the plastic, reduces the heat carried away by the flow of the plastic and the molten droplets, and the extremely poor compatibility with the plastic will lead to uneven plasticization of the entire formulation system and reduce the flame retardant effect. When plastics containing silicon powder burn, stable silicon bromide will be formed on the surface, which will interfere with the gas phase flame retardancy of the plastic. Plastics containing calcium carbonate have an antagonistic effect on flame retardancy and will increase the amount of flame retardant used. Therefore, in the selection of nucleating agents, the influence of inorganic nucleating agents on the formulation is negative.
[0061] In summary, the halogen-free flame-retardant nylon composite material prepared in the embodiment of the present invention perfectly solves the "wick effect" problem of MCA flame-retardant nylon, has the characteristics of being able to stably achieve flame retardancy V0, and can be produced in large quantities for a long time. Its raw materials are all commercially available, the preparation process is simple, the cost is relatively low, and it can meet various application requirements of halogen-free flame-retardant nylon in the market, and is particularly suitable for application in the electronic and electrical industry, and has good development prospects.
[0062] The above is a detailed introduction to a halogen-free flame-retardant nylon composite material provided by the present invention. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea; at the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A halogen-free flame-retardant nylon composite material, characterized in that: Made from the following raw materials in parts by weight:
2. The halogen-free flame-retardant nylon composite material according to claim 1, characterized in that: The nylon resin is nylon 66, nylon 6, or one or a mixture of other aliphatic polyamides.
3. The halogen-free flame-retardant nylon composite material according to claim 1, characterized in that: The halogen-free flame retardant is melamine cyanurate (MCA).
4. The halogen-free flame-retardant nylon composite material according to claim 1, characterized in that: The nucleating agent is a sorbitol acetal nucleating agent.
5. The halogen-free flame-retardant nylon composite material according to claim 1, characterized in that: The heat stabilizer is N,N'-bis(2,2,6,6-tetramethyl-4-yl)-1,3-benzenedicarbamide.
6. The halogen-free flame-retardant nylon composite material according to claim 1, characterized in that: The dispersant is distilled water.
7. A method for preparing a halogen-free flame-retardant nylon composite material, characterized in that: The following steps are involved: ① Weigh the raw materials according to the aforementioned weight ratio; ② Add nylon resin and dispersant additives into a high-speed mixer and mix for 3-10 minutes, then add halogen-free flame retardant, nucleating agent, and heat stabilizer and mix for 15-30 minutes; ③ The mixture obtained in step ② is placed in a twin-screw machine, melt-extruded, and granulated, wherein the screw aspect ratio is 32-48, and the process conditions are: zone 1 temperature 200-240°C, zone 2 temperature 230-270°C, zone 3 temperature 200-240°C, zone 4 temperature 220-260°C, die head temperature 240-280°C, barrel residence time 0.5-2 minutes, and melt pressure 10-20 MPa.
Citation Information
Patent Citations
Polyamide resin composition
CN101679743A
Halogen-free flame-retardant nylon composite material and preparation method thereof
CN105062062A
Flame-retardant nylon 66 composite material and preparation method thereof
CN110540750A
Halogen-free flame-retardant nylon material and preparation method thereof
CN112409785A
Flame retardant-stabilizer combination for thermoplastic polymers
CN103140547A
Cited By
Phosphorus-nitrogen synergistic flame-retardant high-temperature-resistant nylon material and preparation method thereof
CN122878749A